A empatia na prática interacional: o caso da relação médico/a e gestantes de médio e alto risco no Sistema Único de Saúde (SUS) - Mossmann, Carina Maria Hilgert (Universidade do Vale do Rio dos Sinos, 2015)
This study is part of a larger project (OSTERMANN, 2013) and aims to describe and systematize empathy by means of an interactional perspective. Having been the subject of several fields of study (Philosophy, Sociology, Anthropology, Psychology, Psychiatry and, more recently, Neurophysiology), there are some definitions to empathy. Such definitions, however, tend to be theoretical and subjective in character, hindering the comprehension of how empathy is realized in interactional practice. In this study, we aim to advance towards the description of empathy so as to reveal the ways it is manifested in practice. Such investigation is carried out by means of empirical analysis and by following the principles of Conversation Analysis (SACKS, 1992; SACKS, SCHEGLOFF, JEFFERSON, 1974). The data used in this study come from a public health system hospital (Sistema Único de Saúde (SUS)), located in the southern Brazil. The data consist of interactions that took place during obstetric and morphological ultrasound exams and fetal echocardiography exams. These exams were carried out at the department of the hospital that is responsible for moderate and high-risk pregnancies. The study reveals that active-listening tends to be a key-element in the interactional sequences in which empathy is observed. The action of active-listening, on its turn, is tied to the interactant’s agentiviy (CLAYMAN, 2012). As a result, we can claim that the patient’s interactional actions during the medical consultations are fundamental elements so as the doctor may have the possibility of undertaking emphatic actions. It is in the sequence of interactional actions, that is, in the co-construction of an interaction, that a socially accomplished empathic relationship may be established. In this sense, it becomes evident that empathy does not emerge tied to a single type of turn design. The data also reveal recurrences in which actions potentially empathic emerge, so that empathy becomes apparent as either a constitutive or an absent element of the several layers that form an interaction action. As a result, an interactional action might be oriented by “something else” which, inside of certain sequential and interaction context, will make it empathic or not. Based on this study, empathy has been defined as a subjective phenomenon that emerges in the interaction by means of different practices and as a way to permeate altruistic or non-altruistic actions.
Keywords: Empatia; Análise da conversa; Medicina; Gestações de risco; Ultrassonografias; Empathy; Conversation analysis; Medicine; Risky pregnancies; Ultrasonographies; ACCNPQ::Lingüística, Letras e Artes::Lingüística